The jumping spider genus Papuaneon Maddison, 2016 (Araneae: Salticidae) in Australia - Richardson, Barry J. (Zootaxa, 2022)
The description of the monotypic genus Papuaneon Maddison, 2016 was based on two specimens of Papuaneon tualapa Maddison, 2016 from Papua New Guinea. This species, plus five new species, namely Papuaneon eungella n. sp., Papuaneon eurobodalla n. sp., Papuaneon ewingar n. sp., Papuaneon tapin n. sp. and Papuaneon werrikimbe n. sp., are described from eastern Australia. These species occur serially down the east coast of Australia from Cape York to Tasmania.